Correlation analysis of preliminary breakdown and first return stroke process in negative ground flash as a function of northeast and southwest monsoon in tropic - Jamil Alsayaydeh, Jamil Abedalrahim; Mohd Isa, Nur Asyiqin; Baharudin, Zikri Abadi; Zainuddin, Hidayat; Zakaria, Zaihasraf; Abdul Rahman, Ahmad Idil; Ahmad Aizan, Zulkefle; Zainon, Maslan; Mat Hanafiah, Mohd Ariff (Asian Research Publishing Network (ARPN), 2023)
The separation duration of Preliminary Breakdown to the First Return Stroke (PB-RS duration) and the ratio between the highest amplitude pulse of Preliminary Breakdown and the first Return Stroke pulse (PB/RS ratio) were successfully used as a tool by many researchers to determine the relationship between lightning ground flashes and physical changes (latitude, regional and thunderstorm). Malaysia is one of the countries with the highest lightning flash density globally, and the occurrences of ground flashes are mainly due to monsoon seasons. Monsoons in Malaysia are Northeast, Southwest, and two transition periods. However, there is no available information to relate the lightning activities in Malaysia under the influence of all monsoon seasons. The above statements motivated our team to present a new statistical analysis of lightning flashes under two seasons' effects (Northeast and Southwest). 83 out of 332 electric radiation field data (fast fields) from six thunderstorms were selected and analyzed. The data was recorded using a 12-bit high-speed transient recorder (HDO 4024) with a resolution of tens of nanoseconds and sampling of 12.5 MS/s. PB/RS ratio between the monsoons is similar to each other. Whereas, the PB-RS separation, has two factors longer during the Southwest monsoon than during the Northeast monsoon. We classified the PB/RS ratio into four categories (>100%, 50- 100%, 20-50%, and < 20%) as an indication of the preliminary breakdown strength. It found that the weakest pulse train (PB/RS ratio is less than 20%) has shown a longer duration of PB-RS and produces higher lightning return strokes in a negative ground flash than the strong one. The results in this study could be evident that the lower strength of preliminary breakdown is correlated to a lower Low Positive Charge Region (LPCR), which means the initial breakdown process only requires low energy to break the LPCR. Hence, these features have shown the highest number of stroke counts compared to pronounced ones. However, it would be more remarkable if one could provide bulky data for this specific study.